Melanoma molecular subtyping and scoring model construction based on ligand-receptor pairs - Lin, Zexu; Lin, Xin; Sun, Yuming; Lei, Shaorong; Cai, Gengming; Li, Zhexuan (Frontiers in Genetics, 2023)
Melanoma is a malignancy of melanocytes, responsible for a high percentage of skin cancer mortality. Cellular communications within the tumor microenvironment are essential for tumor genesis, growth, metastasis, and prognosis. Our research focused on the role of Ligand-Receptor pairs, a type of cellular communication, played in melanoma prognosis. We screened 131 melanoma prognosis corresponded ligand-receptor pairs by analyzing the TCGA data of melanoma and the 2293 LR pairs retrieved from the connectomeDB2020 database. And further developed subtypes of melanoma according to the expression of these ligand-receptor pairs by Consensus Clustering. Then we using lasso cox regression and stepwise multivariate regression analysis established a ligand-receptor pairs-based scoring model for the evaluation of melanoma prognosis. Our study demonstrated that the ligand-receptor pairs are vital to the molecular heterogeneity of melanoma, and characterized three different melanoma ligand-receptor pairs subtypes with different clinicopathological features, mutation signatures, pathway activations, and immune signatures. We further identified 9 key ligand-receptor pairs and established the scoring model, which effectively correlated with the clinical prognosis, immune pathways, and therapy of melanoma. In sum, we found that ligand-receptor pairs are significantly associated with the prognosis and therapy of melanoma. And our ligand-receptor-based scoring model showed potential for the evaluation of melanoma prognosis and immune therapy outcome prediction, which is crucial to the survival for the patients.